Dampak Keberadaan Wisata Kuliner Wasaka dan Mawarung Baimbai Dalam Mendorong Perekonomian Masyarakat Sungai Jingah Banjarmasin - Diany, Adista Anjar (Fakultas Ekonomi dan Bisnis Universitas Islam DR KH EZ Mutaqien, 2024)
Culture is a whole system of ideas, actions and human works. The culture of the Banjar people who like to talk and “mawarung” is a cultural heritage that can attract tourists because of its traditions. Culinary is a tourism activity that involves the provision of food and beverages. This culture that becomes the tourism sector has an impact on the community's economy. The purpose of this study was to determine the impact of culinary tourism in encouraging the community's economy. The type of research is descriptive qualitative. Data collection techniques using purposive and snowball sampling methods. Data collection techniques using observation, interviews and documentation. Data were analyzed by reducing data, presenting data and drawing conclusions. Based on the results of the analysis, it can be concluded that Wasaka and Mawarung Baimbai culinary tourism have more positive impacts on the community's economy in this sector. The increase in income and the opening of jobs are the most significant things with the existence of this culinary tourism. Unfortunately, the lack of permits and communication with community and government representatives means that these culinary tours are often closed. Promotion is also needed to provide wider information, attract the attention of the younger generation and make the existence of culinary tourism not just a momentary euphoria.